Índice SPAD e trocas gasosas ao longo do dia para diferenciação de cana-de-açúcar sob deficiência hídrica - Brunelli, Marcela Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sugarcane (Saccharum spp.) is a globally important not only for sugar production but also for the production of bioenergy crop. The drought is one of the most important environmental factors limiting the global production of sugarcane. Due to the irregularity rainfall, growers have some dependence of irrigation to maintain production targets. However, the water irrigation is limited and must be rationally utilized not only to reduce wastage, but also to reduce the costs of production and maintenance of productivity. The study and development of tolerant varieties to water stress is crucial for production in areas where water is scarce or limited. It is found, in some cultures, the concentration of chlorophyll and the greening of leaves correlate with tolerance to water stress, but these variables are influenced by different environmental conditions, such as irradiance, air temperature and leaf water conditions, that occur in a large variation during the day. The study aimed to evaluate the influence of water stress and time of assessment on reading the SPAD index on sugarcane. The experiment was conducted in a greenhouse, where RB867515 and RB855453 varieties were evaluated, by water stress or not water stress, in relation to SPAD index, total chlorophyll content, leaf temperature, leaf water potential (ψw), CO2 rate assimilation, maximum quantum efficiency of photosystem II (Fv/Fm), photosynthetic active radiation, temperature and humidity on +1 leaf in four times of the day (7, 10, 13 and 16 hours). Thus, we found the variation of SPAD index during the day, that showed a decreasing tendency over the hours, and it was verified that the total chlorophyll content extracted ranging in the same way. Overall, the most significant results of physiological parameters, except for stomatal conductance, for the maximum quantum efficiency of photosystem II (Fv/Fm) and for the water use efficiency ...

A cana-de-açúcar (Saccharum spp.) é uma cultura globalmente importante não só para a produção de açúcar como também para a produção de bioenergia. A seca é um dos fatores ambientais mais importantes que limita a produção mundial de cana-de-açúcar. Devido à natureza irregular das chuvas, os produtores têm certa dependência da irrigação para manter as metas de produção. Entretanto, a água para irrigação é limitada, e deve ser utilizada racionalmente, não só para reduzir o desperdício, mas também pela redução dos custos de produção e manutenção de produtividade. O desenvolvimento e estudo de variedades tolerantes ao estresse hídrico é crucial para a produção em áreas onde a água é escassa ou limitada. É verificado, em algumas culturas, que a concentração de clorofila e o esverdeamento das folhas se correlacionam com tolerância à deficiência de água, porém essas variáveis recebem influência de diferentes condições ambientais,rever tais como irradiância, temperatura do ar e condições hídricas da folha, que normalmente ocorrem grandes variações durante o dia. O trabalho teve como objetivo avaliar a influência do estresse hídrico e do horário de avaliação sobre a leitura do índice SPAD e das trocas gasosas em cana-de-açúcar. O experimento foi conduzido em casa de vegetação, onde foram avaliadas as variedades RB867515 e RB855453, sob ou não deficiência hídrica em relação a índice SPAD, conteúdo de clorofila total, temperatura foliar, potencial hídrico foliar (ψw), taxa de assimilação de CO2, máxima eficiência fotoquímica do fotossistema II (Fv/Fm), radiação fotossinteticamente ativa, temperatura e umidade do ar na folha +1 em quatro horários do dia (7, 10, 13 e 16h). Para tanto, constatou-se a variação do índice SPAD durante o dia, obtendo uma tendência decrescente com o passar das horas, tendo o conteúdo de ...
Keywords: Cana-de-açúcar - Fisiologia; Secas; Clorofila; Desidratação (Hídrica); Sugar-cane